A formal mathematical framework for modeling and simulation of wireless sensor network environments utilizing the hill-building behavior of termites. (May 2013) - Zungeru, Adamu Murtala; Ang, Li-Minn; Seng, Kah Phooi
The current practice in modeling and simulation of wireless sensor network (WSN) environments is to develop functional WSN systems for event gathering and optimize the necessary performance metric using heuristics and intuition. The evaluation and validation of the WSN system is mostly done using simulation approaches and practical implementations. Simulation studies, despite their wide use and merits for network systems and algorithms validation, have some drawbacks such as long simulation times, and some results reported by several prominent protocols cannot be repeated and are inconsistent. We, therefore, argue that simulation-based validation of WSN systems and environments should be further strengthened through mathematical analysis. To this end, we developed our modeling framework based on energy consumption for WSN topology and information extraction in a grid-based and line-based, randomly distributed sensor network. We strengthen the work with a model of the mobility impact on routing energy consumption by deriving the expected energy consumption of an agent-based reactive routing protocol for a WSN system as a function of packet arrival rate and topology change rate, using a termite hill routing algorithm. The results of our mathematical analysis were also compared with the simulation results.